PERBANDINGAN HASIL BELAJAR BIOLOGI SISWA MENGGUNAKAN STRATEGI PEMBELAJARAN KOOPERATIF NUMBER HEADS TOGETHER DAN READING GUIDE - Nella Paradilla; Misykat Malik Ibrahim; Rafiqah Rafiqah (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2016)
This research aimed (1) To find out the student’s learning outcomes by using learning strategies Numbered Heads Together (NHT) on the material digestive system for students of class XI MAN Pinrang, (2) To find out the student’s learning outcomes by using a learning strategies Reading Guide on material digestive system for students of class XI MAN Pinrang and (3) To find out a significant differences between the results of student’s learning by using learning strategy Numbered Heads Together (NHT) than students who using learning strategy Reading Guide on material digestive system for all students of class XI MAN Pinrang. The type of research used in this study was a quasi-experimental research (quasi- experimental) that used the design of Nonequivalent Control Group Design. The populations in this research were all students of class XI MAN Pinrang in academic year 2015/2016 which consisted of six classes. The technique of sampling used in this research was simple random sampling, selected as the first experimental class was the class XI IPA4 as many as 37 students and selected as second experimental class II was the class XI IPA6 as many as 37 students. Technique of collecting data used by using a test instrument that has multiple choice questions of 25 questions relating to the material digestive system and observation sheet. Technique of data analysis used the descriptive statistical analysis and inferential statistical analysis.The results obtained in both groups through a descriptive statistical analysis were, the average results of studying biology by using learning strategy Numbered Heads Together (NHT) at = 75.16 while the average result of studying biology by using learning strategy Reading Guide amounted to 75.43. The results of inferential data analysis showed that significant value was obtained thitung 9.734> ttabel 1.998 and significance (0.000 <0.05). So, it can be concluded that there were significant differences by using learning strategies between Numbered Heads Together (NHT) with Reading Guide on biology learning outcomes for students of class XI at MAN Pinrang.